Annual World Bank Conference on Development Economics 1998 (Annual World Bank Conference on Development Economics, 1999)
The 1998 Annual World Bank Conference on Development Economics, the tenth anniversary, was held at the Bank on April 20-21, 1998. The discussions focused on four areas of inquiry:1) the role of geography in countries'success, 2) the role of effective competition and regulatory policies, 3) the causes of financial crises and ways to prevent them, and 4) the effects of ethnic diversity on democracy and growth. The welcoming address by World Bank President James D. Wolfensohn, the opening remarks by chief Economist Joseph Stiglitz, and the tenth anniversary address by the International Monetary Fund Deputy Managing Director Stanley Fischer all focused both on the role of the conference and on the changing perspectives for development